Unlawful Acts Committed By A Substitute Notary Regarding the Mortgage Deed they Drafted - Nadia Tasha Juniar; Gunawan Djajaputra (Dinasti Research, 2024)
The role of a notary is indispensable, as notaries are tasked with the duty and obligation to draft authentic legal deeds, which hold great significance, particularly in a legal state such as Indonesia. In certain circumstances, notaries may be required or permitted to take a leave of absence, commonly referred to as notary leave. To prevent any gaps in service, a substitute notary is appointed in accordance with prevailing regulations. These substitute notaries, in fulfilling their duties, are bound by the Law of The Republic of Indonesia Number 30 Of 2004 on Notary Profession. However, in the course of executing their responsibilities, a Substitute Notary may contravene the Law on the Rules of Notary Profession or engage in unlawful act, raising questions regarding the accountability of a Substitute Notary in cases where they commit unlawful acts, such as in verdict number 395/Pdt.G/2011/PN. JKT. Sel. Writing method used in this study is a normative juridical research method.